Design, synthesis and preliminary antiproliferative activity studies of new diheteroaryl thioether derivatives. Issue 18 (15th September 2017) - Li, Zhong-Hua; Liu, Xue-Qi; Zhao, Tao-Qian; Geng, Peng-Fei; Liu, Ying; Zhao, Bing; Guo, Wen-Ge; Yu, Bin; Liu, Hong-Min
Graphical abstract: Highlights: The diheteroaryl thioether derivatives showed potent inhibition against the cancer cells. Compound5 exerted the most potent and broad-spectrum antiproliferative activity. Compound5 induced G2/M arrest of MKN-45 cells. Compound5 induced apoptosis of MKN-45 through the intrinsic apoptotic pathway. Abstract: A series of structurally new diheteroaryl thioether analogs was designed, prepared and screened toward MGC-803, MKN-45, EC-109 and H1650. Most of the target compounds displayed moderate to potent antiproliferative activities. Among them, compound5 showed the best antiproliferative activity against the tested cell lines with the half maximal inhibitory concentration (IC50 ) values below 10 μM. In addition, flow cytometry analysis showed that compound5 increased Bax expression, down-regulated expression of Bcl-2, cleaved caspases-3/9, finally inducing apoptosis of MKN-45 cells as well as arrested the cell cycle at G2/M phase. This study suggests that the diheteroaryl thioethers are a class of emerging chemotypes for developing antitumor agents or biological probes, and compound5 could serve as a good starting point to design new apoptosis inducers.